2011
DOI: 10.1159/000334619
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Management Outcomes of Severe Hand, Foot and Mouth Disease

Abstract: Objective: This study was designed to describe the clinical features and management outcomes of severe hand, foot and mouth disease (HFMD). Subjects and Methods: Data on 147 severe HFMD patients during an outbreak in 2009 were analyzed. Results: Most patients were under 3 years of age; 102 (69.4%) were boys. All had skin rashes and fever of ≥38°C. All (n = 147, 100%) showed signs of central nervous system involvement, such as lethargy (n = 124, 84.4%), myoclonic jerks (n = 76, 51.7%), or drowsiness (n = 34, 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…More interestingly, we also demonstrated that EV71 and CVA16 were co-circulated in this HFMD outbreak. It has been reported that many large outbreaks of HFMD were only EV71-associated [8], [15], [16], [19], [25], [28], [44], [45], [47], [48], [52][54], [57][59], [89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More interestingly, we also demonstrated that EV71 and CVA16 were co-circulated in this HFMD outbreak. It has been reported that many large outbreaks of HFMD were only EV71-associated [8], [15], [16], [19], [25], [28], [44], [45], [47], [48], [52][54], [57][59], [89].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1997, EV71 outbreaks have gained more attention as there is an upward trend in the prevalence of EV71 globally [16], [19], [44][52]. In recent years, many large outbreaks of EV71-associated HFMD with high morbidity and mortality have occurred in the Asia-Pacific region [8], [15], [53][57]. In China, large scale EV71 outbreaks associated with acute neurological diseases were occurred in 2008 [25], [58], and since then the outbreak pattern has repeated and exacerbated each year, with increasing morbidity and mortality [27], [59].…”
Section: Introductionmentioning
confidence: 99%
“…13 Another clinical study on severe HFMD with systemic complications reported that the hips were affected in 53% of patients. 15 The buttocks were affected in 31% of patients with atypical HFMD in a hospital-based prospective study. 6 Moreover, there wasn't a significant difference in the frequency of trunk and scalp involvement according to age group, and the scalp was the least commonly affected.…”
Section: Resultsmentioning
confidence: 97%
“…7 Commonly, HFMD is mild and self-limiting, with relief of symptoms within 7-10 days, but viruses can be detected in the stool for weeks after the symptoms dissipate. 4,8 There are no specific treatments for HFMD at present. The most common treatment is to relieve symptoms by supportive therapy and the application of antivirals, antibiotics and immunopotentiators.…”
mentioning
confidence: 99%
“…The most common treatment is to relieve symptoms by supportive therapy and the application of antivirals, antibiotics and immunopotentiators. 5,8 According to the guidelines issued by the Ministry of Health of China, 9 HFMD should be paid enough attention during the first five days in case it progress into severe conditions without immediate and effective intervention. Traditional Chinese medicine (TCM) was highly recommended by Ministry of Health of China for HFMD treatment.…”
mentioning
confidence: 99%